Reference Management Software Training for Educators - Ansar Suherman; Harry Fajar Maulana; Wa Ode Murmainah; Reza Maulana (Universitas Muhammadiyah Surakarta, 2022)
Teachers in schools not only have to be good at teaching in the classroom, but, like lecturers in higher education, have an obligation to be able to conduct research and compile scientific articles. So it is important for teachers to have mastery in organizing references or literature properly. The use of reference management software is something that teachers must know and be able to use. In general, teachers at SMA 1 Muhammadiyah Baubau do not have the knowledge and skills to use the reference management system, so this community service activity is carried out with the aim of providing knowledge and skills for teachers at SMA 1 Muhammadiyah Baubau regarding reference management software. The applications provided are Zotero, and EndNote, and Mendeley. The activity was held for two days, starting with a survey of participant knowledge and continued with training on reference management software, and ending with a post-test for participants to measure the level of participant mastery. The survey results showed that most of the training participants did not have a good understanding of reference management software including its operation. After the training, 90% of the trainees stated that the Zotero application is quite easy to use when compared to the End-Note application. 54% of participants stated that the Zotero application is easier to operate, while 43% stated that the EndNote application is easier to use, meaning that the two applications are almost as easy to operate. Another finding was that the training participants expressed their satisfaction with the speaker 's mastery of the material including the presentation of the material that was interesting and easily understood by the participants.